ENVIRONMENTAL MANAGEMENT SOFTWARE ADMINISTERED WITH ISO 9001:2008 AND ISO 14001:2004 - Torres, Arturo Gonzalez; Montero, Fatima Y. Mendoza; Romero, Fernando Terreros; Ojinaga, Eduardo Rafael Poblano; Reyes, Sara Maria Velazquez; Barraza, Elisa Urquizo; Carrillo, Maria Cristina Garcia (European Scientific Journal, ESJ, 2014)
The aim of this project is the creation, design and implementation of managed software with ISO 9001:2008 and ISO 14001:2004, which will optimize the process of material resources department in the shopping area in Higher Education Institution. A study was conducted to identify the weaknesses of the department found that in filling the formats is done traditionally, with the result that it is susceptible to errors at the time of capture, the time spent is high paper costs and ink are unnecessary and also not have an effective management and control of the data required by the query difficult formats. The developed software covers the weaknesses found, and was implemented under tools provided by the Institute by making the cost of it is relatively minor compared to commercial software, and the software itself is administered with ISO quality and environment therefore is functional for both the Higher Education Institution to any Technology of Mexico. Based on the research results, the software will be implemented on a trial period of six months in the material resources department, in the shopping area in Higher Education Institution evaluate the results and to use the software for and care for the environment and be able to promote to the Dirección General de Educación Superior Tecnológico.